1993
DOI: 10.1016/0140-6736(93)90064-n
|View full text |Cite
|
Sign up to set email alerts
|

Cysticercosis as a major cause of epilepsy in Peru

Abstract: In countries where cysticercosis is endemic, the proportion of epilepsy due to cysticercosis is not well documented. To investigate the association between cysticercosis and epilepsy, we used the enzyme-linked immunoelectrotransfer blot (EITB) assay to detect serum antibodies to Taenia solium in 498 consecutive outpatients at a neurology clinic in Lima, Peru. Every patient was classified as epileptic (n = 189) or non-epileptic (n = 309) after neurological, and where possible electroencephalographic, examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
92
1
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(98 citation statements)
references
References 18 publications
2
92
1
3
Order By: Relevance
“…Studies based on hospital series have reported that 50% of the 100 patients studied in Mexico have neurocysticercosis as the main cause of late-onset epilepsy (Medina et al, 1990). In a large series studied in Colombia and Peru where EITB method was used, cysticercosis was proven as the cause of epilepsy in 14% and 12% of the cases, respectively (Garcia et al, 1993, Palacio et al, 1998. It must be noted that there are very few studies on the neurocysticercosis in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on hospital series have reported that 50% of the 100 patients studied in Mexico have neurocysticercosis as the main cause of late-onset epilepsy (Medina et al, 1990). In a large series studied in Colombia and Peru where EITB method was used, cysticercosis was proven as the cause of epilepsy in 14% and 12% of the cases, respectively (Garcia et al, 1993, Palacio et al, 1998. It must be noted that there are very few studies on the neurocysticercosis in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Increased seropositivity among family members of individuals with neurocysticercosis has been shown before in previous investigations in rural communities of Peru, Mexico, and Guatemala. 4,8,11 However, the earlier studies have focused on the prevalence of cysticercosis in rural areas and communities with lower socio-economic status. [8][9][10][11] These studies reported a seroprevalence of human cysticercosis of 8% in Peru, 4 10.8% in Mexico, 8 and from 10% to 17% in Guatemala.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,11 However, the earlier studies have focused on the prevalence of cysticercosis in rural areas and communities with lower socio-economic status. [8][9][10][11] These studies reported a seroprevalence of human cysticercosis of 8% in Peru, 4 10.8% in Mexico, 8 and from 10% to 17% in Guatemala. 11 Our study demonstrates a high background rate of seropositivity for cysticercosis, 3.8%, among an urban, middle to upper-middle class population, suggesting that socioeconomic status does not seem to mitigate against seropositivity in a region that is hyperendemic for T. solium taeniasis and cysticercosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations